The role of compensation in shaping employee’s behaviour: a mediation study through job satisfaction during the Covid-19 pandemic - Attia Aman-Ullah; Azelin Aziz; Hadziroh Ibrahim; Waqas Mehmood; Attiqa Aman-Ullah (REGE Revista de Gestão, 2023)
Purpose – This research aimed to study the impact of compensation on employee retention and turnover intentions among healthcare employees. The study also tested the mediation role of job satisfaction in the relationship. Design/methodology/approach – In the present study, self-administrated questionnaires were distributed among 600 doctors working in public hospitals of Pakistan, following stratified sampling. The data analysis was conducted through SPSS and smart-PLS. Findings – Results of the present study supported all the hypotheses (H1–H7), such as the significant relationship of compensation with employee retention and turnover intentions. Results further confirmed the mediation effect of job satisfaction between compensation and employee retention as well as compensation and turnover intentions. Practical implications – This study is useful for policymakers and organizational managers since the study provides guidelines on employee retention and high turnover intentions and how these factors are influenced by improved compensation. Originality/value – This study sheds light on the relationship of compensation together with employee retention and turnover intentions through the mediating role of job satisfaction in healthcare context, which was overlooked in the existing literature.